Pengaruh Model Problem Based Learning Berbantuan Media Pembelajaran Interaktif Berbasis Canva Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Pada Kelas VIII SMP Swasta An-Nizam Medan - Marhani, Hajar; Ananda, Rusydi; Hasanah, Rusi Ulfa (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
Problem solving is the ability of students to find solutions to problems by using the knowledge, skills, and understanding they already have. However, in reality, students’ mathematical problem solving is still relatively low. This study aims to analyze the effect of the problem-based learning model assisted by interactive learning media based on canva on the mathematical problem solving abilities of class VIII students of An-Nizam Medan Private Middle School. This study is a quantitative study with a quasi-experimental research method using a Non-Equivalent Control Group design. The sample used was two classes totaling 40 students where class VIII-ha as the experimental class and VIII-khd as the control class, each consisting of 20 students. The research sampling technique used cluster random sampling technique. The data collection method used by researchers was the distribution of pretest and posttest. The results of the study showed that the average N-gain score of class VIII-HA which is the experimental class was 77.00 and the average N-gain score of class VIII-KHD which is the control class was 64.01. This result can be proven by the results of the hypothesis test which shows a significant value of 0.002 < 0.05. Thus, ???????? is rejected and ???????? is accepted, which means there is an influence of the problem-based learning model assisted by interactive learning media based on Canva on the mathematical problem-solving abilities of eighth-grade students of An-Nizam Private Middle School, Medan.